SISTEM MONITORING JARINGAN WIFI MENGGUNAKAN WIRESHARK PADA STMIK KNI KRISTEN NEUMANN INDONESIA - Bersama Sinuraya; Heryco Bremana P Tarigan (UPPM, 2016)
STMIK Neumann is one college that was founded by YPK-GBKP. Where on campus STMIK Neumann already have WIFI, WIFI network even though the network is not connected to the rest of the room. Wireshark is being used to monitor WIFI in order to capture the packet and the frames in the STMIK Neumann WIFI. Where to help us in monitoring the WIFI network we are using Wireshark, then this final task in the analysis and monitored from a network that is running by using Wireshark, where in if the network is connected in a campus STMIK Neumann with expectations when using wireshark help us in monitoring the WIFI network which captures all kinds of networks that are running or are being connected to the campus network STMIK Neumann.